Single spore isolation and hybridization of Calocybe spp. - S, VIJETH; GANGADHARAN, HEERA (Mushroom Research, 2022)
A study was conducted at Department of Plant Pathology for the development of improved strain(s) of Calocybe spp. with desirable traits by interspecific hybridization. Milky white mushroom (C. indica) and St. George’s mushroom (C. gambosa) were the species used for hybridization. Pure culturing and morphological characterization of sporocarp of Calocybe spp. was done. In vitro evaluation of both the species for mycelial characteristics, growth rate, colony colour, days taken for completion of full growth were recorded. Single spore isolation was done through serial dilution technique. Hybridisation of single spores was done by dual culture technique using hyphal anastomosis for the development of hybrids. Of the 121 crosses done 22 were compatible and 79 crosses incompatible. Keywords: Calocybe indica, C. gambosa, Interspecific hybridization, mycelial growth rate.